2014
DOI: 10.1073/pnas.1320827111
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous organization of the locus coeruleus projections to prefrontal and motor cortices

Abstract: The brainstem nucleus locus coeruleus (LC) is the primary source of norepinephrine (NE) to the mammalian neocortex. It is believed to operate as a homogeneous syncytium of transmitter-specific cells that regulate brain function and behavior via an extensive network of axonal projections and global transmitter-mediated modulatory influences on a diverse assembly of neural targets within the CNS. The data presented here challenge this longstanding notion and argue instead for segregated operation of the LC-NE sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
230
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(254 citation statements)
references
References 46 publications
15
230
0
Order By: Relevance
“…Our proof-of-principle application of RC::FLTG and RC::RFLTG to analysis of the central noradrenergic system confirms the value of key features of these alleles. There are no molecular markers known to uniquely label subpopulations of noradrenergic neurons, so investigation of noradrenergic neuron heterogeneity, particularly axon projection patterns, depends either on genetic intersectional labeling (Robertson et al, 2013) or strategies for retrograde labeling by injection of dyes or viruses at target sites (Chandler and Waterhouse, 2012;Chandler et al, 2013Chandler et al, , 2014Schwarz et al, 2015). The ability of RC::FLTG to label axons of the entire noradrenergic system, subdivided between an intersectional and a subtractive population, reveals diversity of noradrenergic projections at target sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our proof-of-principle application of RC::FLTG and RC::RFLTG to analysis of the central noradrenergic system confirms the value of key features of these alleles. There are no molecular markers known to uniquely label subpopulations of noradrenergic neurons, so investigation of noradrenergic neuron heterogeneity, particularly axon projection patterns, depends either on genetic intersectional labeling (Robertson et al, 2013) or strategies for retrograde labeling by injection of dyes or viruses at target sites (Chandler and Waterhouse, 2012;Chandler et al, 2013Chandler et al, , 2014Schwarz et al, 2015). The ability of RC::FLTG to label axons of the entire noradrenergic system, subdivided between an intersectional and a subtractive population, reveals diversity of noradrenergic projections at target sites.…”
Section: Discussionmentioning
confidence: 99%
“…Wide-ranging evidence indicates the importance of galanin in noradrenergic neurons and possible functional differences between galanergic and non-galanergic LC neurons (Sevcik et al, 1993;Miller et al, 1999;Sciolino et al, 2015). However, despite evidence that the LC contains neurons with distinct projection profiles (Chandler and Waterhouse, 2012;Chandler et al, 2013Chandler et al, , 2014, the subpopulations distinguished by Gal-Cre expression show no gross difference in their axonal targets. This surprising result is compatible with the recently reported finding that specifically activating the Gal-Creexpressing LC subpopulation has the same effect on aversive behavior as activating the whole LC (McCall et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A related follow-up study found that these unique subpopulations of LC neurons projecting to OFC, mPFC, and ACC were also distinct from another population of LC neurons projecting to motor cortex (M1) ( Fig. 1C; Chandler et al 2014a). Importantly, OFC and mPFC projecting LC neurons displayed a different molecular profile from M1 neurons, expressing higher transcript levels of proteins associated with glutamatergic transmission and excitability.…”
Section: Anatomical Connectivity and Efferent Specificity In Lc Neuronsmentioning
confidence: 93%
“…Based on the evidence presented above including previous anatomical/physiological studies showing projection specificity in the LC system (Chandler and Waterhouse 2012;Chandler et al 2013Chandler et al , 2014a we propose a conceptual, hypothetical model of LC function in which distinct subpopulations of LC noradrenergic neurons modulate specific aspects of learning and memory based on their projection specificity. Specifically, we propose that anatomically distinct populations of LC neurons project to either the amygdala or mPFC (Fig.…”
Section: A Hypothetical Model Of Lc Function During Learning and Memorymentioning
confidence: 94%